PENDIDIKAN MENJAGA LISAN DAN ETIKA BERKOMENTAR : REFLEKSI AJARAN ISLAM DI DUNIA MAYA - Evi Febriani; Dinda Ramadani Amir; Dita Putri; Muhamad Kumaidi; Dwi Novfitriani Antoni Putri; Elsa Melinda Efani MNG; Cut Eva Novita Restu (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
In today’s digital era, everyone can easily express their opinions through social media. However, this freedom is often misused, leading to harsh comments, slander, and hate speech. This article discusses the importance of guarding one’s speech and maintaining proper etiquette in commenting, based on Islamic teachings. In Islam, every word—spoken or written—carries moral responsibility and will be held accountable before Allah. The principle of “speaking good or remaining silent” serves as a fundamental guideline in all forms of communication, including online interactions. Through an analysis of verses from the Qur’an and Hadith, this article emphasizes that guarding one’s speech in the digital space is not only about politeness but also reflects one’s faith and character. By applying Islamic values in online communication, social media can become a medium for spreading goodness rather than a place for harm or conflict.